Comparative evaluation of various DNA extraction methods and analysis of DNA degradation levels in commercially marketed Chestnut rose juices and beverages - Yongchao Ren; Yunlong Ma; Yanqi Li; Yun Song; WeiWei Zhao; Xuncai Huang; Danmin Yu; Jian Li; Zuogang Xu; Wenjun Zhao (BMC Biotechnology)
Abstract Background Food safety is a significant global study subject that is strongly intertwined with human life and well-being. The utilization of DNA-based methods for species identification is a valuable instrument in the field of food inspection and regulation. It is particularly significant for traceability purposes, as it enables the monitoring of a specific item at every level of the food chain regulation. However, obtaining amplifiable genomic DNA in this process is a significant obstacle in gene studies. To date, there is a lack of literature on DNA extraction from processed juice or beverages, and no data exist on simultaneous comparisons of various extraction processes. This study aimed to optimize and compare four DNA extraction methods for Chestnut rose juices and beverages. Furthermore, we also conducted a comparison and analysis of the extent of DNA degradation in Chestnut rose juice or beverage by utilizing the amplicon size. Methods The quantity and quality of the extracted DNA were assessed using NanoDrop One spectrophotometer, gel electrophoresis, and real-time polymerase chain reaction (real-time PCR or qPCR) assays. An assessment was conducted on the processing time, labor intensity, and cost associated with each approach. The degree of DNA degradation in Chestnut rose juice or beverage was also assessed using TaqMan real-time PCR methods. Results The non-commercial modified CTAB-based approach yielded a high DNA concentration. However, spectrophotometric results and real-time PCR analysis showed poor DNA quality. The combination approach showed the greatest performance among the extraction methods, while being comparatively time-consuming and costly in contrast to the other methods. Additionally, the analytical findings of DNA degradation suggested that the integrity of sample DNA could be influenced by the intricacy of processing methods used by various manufacturers. Conclusions To achieve precise DNA quantification, selecting suitable extraction strategies for the given matrix is necessary. The combination approach was identified as the most effective DNA extraction technique and is suggested for extracting DNA from Chestnut rose juices and beverages. This comparative assessment can be particularly valuable for extracting and identifying processed Juices and Beverages in a diverse range of food compositions.